Orbitary-palpebral abscess. Acute rhinosinusitis was not healed - Rodríguez Pérez, Miguel Alberto (2017)
Case Report: We present a case report in a 20-year-old boy who attended the Emergency Unit with proptosis, redness and righteye- swelling, fluctuating in palpation, accompanied by fever and moderate flu symptoms. He had been suffering from a severe acute rhinosinusitis with abundant nasal mucus for some weeks before, that regarding the evolution, was undertreated.Discussion: After CT scan and diagnosis of orbitary abscess as a result of an acute rhinosinusitis complication, the patient underwent surgical drainage and appropriate intravenous antibiotic and corticosteroid therapy. He recovered in a few days, and the microbiology results revealed aerobic and anaerobic germs (Streptococcus intermedius and Eikenella corrodens).